High dietary live microbe intake associated with reduced depressive symptoms in gastrointestinal disease patients: findings from a cross-sectional study - Cheng Zhang; Ming-Hui Ma; Ke Li; Shu-Ning Xu; Ying Liu (Nutrition & Metabolism)
Abstract Background Depression and gastrointestinal disease are prevalent conditions that often coexist, significantly impacting daily life and productivity. Recent studies suggest a potential link between the intake of dietary live microbe and the alleviation of depressive symptoms. However, the relationship between live microbe consumption and depressive symptoms in patients suffering from gastrointestinal diseases remains unexplored. Methods This study included participants with gastrointestinal diseases from the National Health and Nutrition Examination Survey (NHANES) spanning from 2005 to 2018. We utilized weighted multivariate logistic regression, subgroup analyses, and restricted cubic spline (RCS) analyses to investigate the association between live microbe consumption and depression. Additionally, the eXtreme Gradient Boosting (XGBoost) algorithm was implemented to develop a predictive model for depression based on individual characteristics. Results Of the 2,195 individuals, 472 (21.5%) exhibited depressive symptoms (PHQ-9 ≥ 10). Our findings indicate an inverse relationship between the live microbe intake and the incidence of depression in individuals with gastrointestinal diseases. In the most comprehensively adjusted model, patients with the highest level of microbe intake exhibited a 66.1% or 52.9% reduced risk of depressive symptoms compared to those with the minimal intake. An L-shaped dose-response relationship was observed in the RCS analysis (non-linear P = 4e-04). The XGBoost model demonstrated effective prediction capabilities for depression, with an area under the curve (AUC) of 0.897 (95% CI: 0.869–0.925). Conclusions This study provides evidence of an inverse, non-linear association between dietary live microbe and depression in individuals with gastrointestinal diseases, suggesting that higher intake levels may offer protective effects against depressive symptoms.